The Lattice of Intuitionistic Fuzzy Filters in Residuated Lattices - Zhen Ming Ma (Journal of Applied Mathematics)
The notion of tip-extended pair of intuitionistic fuzzy filters is introduced by which it is proved that the set of all intuitionistic fuzzy filters in a residuated lattice forms a bounded distributive lattice.